Pengaruh Brand Image Dan Brand Trust Terhadap Loyalitas Pengguna Helm KYT - Muhammad Awal; Aldisa Arifudin; Florentina B Parapaga (Musamus Journal of Business & Management, 2022)
The purpose of this research is to examine the impact of brand trust and brand image on the brand loyalty of KYT brand helmet consumers in the city of Merauke. The technique employed is a quantitative method. The sample for this research was comprised of 70 persons, and the respondents had to be KYT helmet users who reside in Merauke and its surroundings, are at least 17 years old, and have made at least one repeat purchase. The program SPSS version 25 is used to do multiple regression analysis as the analysis methods. In hypothesis testing, the results obtained are 0.04 < from a significant level of 0.05, then brand image has a significant effect on loyalty, while 0.001 < from a significance level of 0.005 means brand trust has a significant influence on customer loyalty. Furthermore, by using the f test obtained 0.001 < from the significance level of 0.005 then brand image and brand trust simultaneously affect loyalty. The results indicated that brand image and brand trust had an influence on customer loyalty, either concurrently or partially, with a magnitude of 76.3% and the remaining 23.7% affected by variables not researched in this research